Prabowo and The Gemoy Image in the 2024 Presidential Election Campaign Gerindra TV's YouTube - Muhammad Asnan; Indah ayu Puspita; Agung Purnomo (International Journal of Multidisciplinary Applied and Science Research, 2025)
This research was conducted with the aim of understanding Prabowo and the Gemoy Image in the 2024 Presidential Election. The author has a sub-research focus, namely a Study of the Image Building of Presidential Candidate Prabowo Subianto in the 2024 Election Campaign through Animated Advertisements on YouTube Gerindra TV. The analytical method used in this research employs the Charles Sanders Peirce semiotic analysis method along with other theories to understand how Prabowo and the Gemoy Image are positioned in the 2024 Presidential Election. The results of this research reveal the portrayal of Prabowo and the Gemoy Image in the 2024 Presidential Election within the Animated Advertisement on YouTube Gerindra TV. The campaign presented in this animated advertisement features the figure of Prabowo in animated visuals accompanied by musical accompaniment and song lyrics that state the vision, mission, and programs promoted by the presidential candidate pair Prabowo Subianto and Gibran Rakabuming Raka.